Movement of long-tailed ducks marked on the Yukon-Kuskokwim Delta, Alaska 1998-2000 (data from Petersen et al. 2003) - Petersen, Margaret R.; Douglas, David C. (Movebank Data Repository, 2016)
Petersen MR, McCaffery BJ, Flint PL (2003) Post-breeding distribution of long-tailed ducks Clangula hyemalis from the Yukon-Kuskokwim Delta, Alaska. Wildfowl 54:103-113. : Breeding populations of Long-tailed Ducks Clangula hyemalis have declined in western Alaska, particularly on the Yukon-Kuskokwim (Y-K) Delta, and the species is currently considered a species of particular concern by the U.S. Fish & Wildlife Service in Alaska. Potential factors that may have contributed to this decline that occurred away from the breeding grounds could not be considered since moulting and wintering areas for this population were unknown. A study was conducted in 1998 and 1999 to locate the moulting and wintering areas of the Y-K Delta breeding population. VHF and satellite transmitters were deployed to identify areas used by moulting birds. Based on the locations identified by satellite telemetry, aerial surveys were flown to locate birds marked with VHF transmitters, then low-level aerial surveys were designed and conducted to determine the number of birds using these and adjacent areas. Moulting locations of 54 marked female Long-tailed Ducks were identified: 13 marked females were found in wetlands and large lakes on the Y-K Delta, 11 in coastal lagoons at St Lawrence Island, Alaska, and two along the coast of the Chukotka Peninsula, Russia. A autumn staging area was identified along the east coast of the Chukotka Peninsula which was used by seven of 10 birds with satellite transmitters providing locations during that period. Birds wintered in coastal waters of the North Pacific Ocean north of 50°N and between 150°E and 130°W. The wide distribution of birds in winter suggests little probability of a single factor in winter contributing to the decline.